Perlindungan Hukum terhadap Hak Perempuan dalam Perkawinan menurut Hukum Islam di Indonesia - Jannata, Salsabila; Zahara, Fuzia; Yonanda, Intan; Azzahra, Aulia; Adilano, Abyan; Baidhowi (Indonesian Journal of Law and Justice, 2025)
Legal protection of women's rights in marriage from the perspective of Islamic Law in Indonesia is a crucial aspect in ensuring justice and gender equality within the family environment. This article examines various women's rights in marriage such as the right to dowry, maintenance, consent to marriage, protection from violence, and the right to file for divorce in accordance with the provisions of Law No. 16 of 2019, as an amendment to Law No. 1 of 1974, and the principles set forth in the Compilation of Islamic Law. Although normative regulations accommodate these rights, various challenges remain in practice, particularly due to the strong patriarchal culture, narrow interpretation of religious texts, and lack of legal education for women. The study employs a qualitative approach with juridical and socio-cultural analysis of the application of Islamic law in society. Findings indicate that structural and socio-cultural barriers remain major obstacles to the effective protection of women's rights. Therefore, this article recommends contextual and inclusive fiqh renewal, strengthening law enforcement by religious courts, and public education to raise legal awareness and gender equality. Through the adoption of these recommendations, it is projected that legal protection for women in marriage will be more optimal and in accordance as guided by the principles of justice within Islamic law and Indonesian national law.